The Role of Physical Education and Sports in Shaping National Character - Furkan Furkan; Salahudin Salahudin (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The main objective of this research is to investigate the influence of physical education on the growth and development of student's character. This particular teaching methodology aims to shape the individual's personality holistically by promoting physical activity. The positive impact of this approach is not restricted to the mental sphere alone but also extends to the moral and ethical aspects of students' character. This study aims to explore the various ways in which physical education can enhance the overall caliber of students by promoting their physical fitness, mental well-being, and character development. Materials and Methods. Integrating character development with physical education through a character-based education approach can prove to be an effective way to enhance the overall development of an individual. This approach can holistically improve various aspects of an individual's growth, such as cognitive, physical, social-emotional, creative, and spiritual development. The research on this topic has been conducted using qualitative methods that rely on descriptive data obtained through literature studies. Results. Personality denotes a unique configuration of cognitive, affective, and behavioral traits that distinguishes an individual and shapes their interpersonal dynamics within various social units, ranging from the microcosm of the family to the macrocosm of the nation-state. The overarching objective of personality development is to engender individuals who embody values such as fidelity, integrity, physical and psychological well-being, erudition, understanding, originality, self-sufficiency, and civic accountability. In this regard, the domains of physical education and sports assume an instrumental role in fortifying and honing individual character through targeted interventions that address physical fitness, motor skills, psychological resilience, and ethical conduct. Conclusion. Various studies have shown that implementing physical education methodologies in school curricula can positively impact students' psychological and character development. This means that physical activities and exercises can help students not only improve their physical health but also their mental and emotional well-being, as well as their social skills and moral values. Therefore, it is important to recognize the significant role that physical education can play in promoting a holistic and well-rounded education for students.